The Influence of Mathematical Understanding, Reasoning, and Resilience on Mathematical Literacy in Karimun Regency's Eighth Graders - Ummi Fadilah Harahap; Jarnawi Afgani Dahlan; Trisno Ikhwanudin (Jurnal Pendidikan Matematika (JPM), 2025)
Mathematical literacy remains a significant concern among students in Indonesia, as reflected in low scores on international assessments such as PISA and TIMSS. This study aimed to examine the impact of mathematical understanding, reasoning, and resilience on the mathematical literacy of 100 8th-grade students in public junior high schools in Karimun Regency. A quantitative approach with a survey design was employed, and data were collected using validated questionnaires and tests. The data were examined using multiple linear regression approach. The results indicated a significant positive relationship between mathematical understanding, reasoning, and resilience on students' mathematical literacy. These findings highlight the need for comprehensive teaching strategies that integrate these three aspects to effectively enhance mathematical literacy. More varied teaching methods and strong support from educators are recommended to optimize students' mathematical literacy.